Structural racism and the deaths of blacks from COVID-19 (Research, Society and Development, 2022)
Introduction: The structural racism to black people generated an attempt to hide the large number of deaths of these by COVID-19, in which racism, existing social inequalities and a public health policy insensitive to the real needs of the majority of the population joined. Objective: To establish a reflection about "Necropolitics and reflections about the black population in the context of the pandemic of COVID-19 in Brazil: a literature review" within the philosophical perspectives, the concepts of structural racism, institutional racism, necropolitics, brand prejudice and the mandatory inclusion in epidemiological records of the race/color of the victimized people. Methodology: an integrative review was carried out, data found, were established descriptively and reflexively with the philosophical perspectives predefined. Results and discussion: Although this review allowed access to this information, such not sufficient to overcome the structural racism, brand prejudice and exclusion of black people affected by COVID-19. But, it reveals a racist, exclusionary, and statist society similar to those with eugenic and obscure practices in dealing with the health of black and poor people. Final considerations: It was observed that even in the contemporary world, for structural and historical reasons, black people are more susceptible to the contagion and evolution of the COVID-19, not directly due to biological causes of their skin color or because they have a more fragile body, but by eclipsing a health policy that excludes the issues of racism and social and economic inequalities in its concrete action to combat the pandemic.